2015
DOI: 10.1177/1535370214548996
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular regulated protein kinases 1/2 phosphorylation is required for hepatic differentiation of human umbilical cord-derived mesenchymal stem cells

Abstract: Mesenchymal stem cells (MSCs) have the capacity to restore liver function by differentiating into hepatocyte like cells. However, the underlying mechanisms are not well understood. Here, we have investigated the signals involved in the hepatic differentiation of human umbilical cord-derived mesenchymal stem cells (hUCMSCs). hUCMSCs were treated with mouse fetal liver-conditioned medium (FLCM) to induce hepatic differentiation. Flow cytometry, reverse transcription PCR, real-time PCR, immunocytochemistry, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…RICK is able to regulate the downstream signal through the above pathways (Jeong et al, 2013; H. S. Kim et al, 2013). ERK1/2 phosphorylation is observed in the differentiation of MSCs to multiple lineages (Yan et al, 2015; Zhang et al, 2015). The ERK signaling pathway is involved in odontogenic differentiation of stem cells originating from the apical papilla (SCAPs) and exfoliated deciduous teeth (SHED; Liu et al, 2019; Mu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…RICK is able to regulate the downstream signal through the above pathways (Jeong et al, 2013; H. S. Kim et al, 2013). ERK1/2 phosphorylation is observed in the differentiation of MSCs to multiple lineages (Yan et al, 2015; Zhang et al, 2015). The ERK signaling pathway is involved in odontogenic differentiation of stem cells originating from the apical papilla (SCAPs) and exfoliated deciduous teeth (SHED; Liu et al, 2019; Mu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Conditioned medium: Previous findings have suggested that, under defined conditions ( e.g ., a simulated normal liver microenvironment), hUC-MSCs can differentiate into functional hepatocytes. Yan et al[74] explored the use of fetal liver-conditioned medium for hepatic differentiation of hUC-MSCs. The expression of MSC-specific markers decreased, while hepatocyte-specific gene expression was increased.…”
Section: Characteristics Of Huc-mscsmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) have gained attention for their potential in treating various diseases, advancing from animal experiments to clinical trials (1), and MSC biosafety has been widely indicated. We defined the renovation of MSCs in hepatic diseases over a decade ago using an in-house isolation culture system (2)(3)(4)(5)(6)(7). MSCs differentiate into hepatocyte-like cells (8), informing the transition from liver to hepatocyte transplantation to improve liver function.…”
Section: Introductionmentioning
confidence: 99%
“…The capacity of MSCs to reverse mouse hepatic injury (2) and Schistosoma japonicum-induced mouse liver injury was also shown (7). ERK1/2 phosphorylation was defined as an essential factor for differentiation (3), and concurrent overexpression of miR-106a, miR-574-3p, and miR-451 was shown to induce human umbilical cordderived MSC (hucMSC) differentiation into functionally mature hepatocytes (9).…”
Section: Introductionmentioning
confidence: 99%